(untitled) (Bangladesh Journal of Nutrition, 2020)
Child malnutrition is a great public health issue and for that reason adequate nutrition is identified as one of the pillars of public health. This present study aimed to explore the extent of child malnutrition as well as factors associated with undernutrition and Low Birth Weight (LBW) in Cumilla. A cross sectional study was conducted in selected areas of Cumilla district in April, 2019. In total 355 households were included in the study following inclusion criteria and 299 under five children was assessed for anthropometry. SPSS (version 25) and WHO Anthro (version 3.3.2) was used for analytical purpose. Prevalence of LBW was 18.6% and mean (SD) birth weight was 2.54 (0.78) kg. Important covariates for LBW were uneducated mother (AOR = 1.32, p < 0.001), household food security (AOR = 0.81, p < 0.001) and intake of iron tablet during pregnancy (AOR = 0.56, p < 0.05). Prevalence of stunting, wasting, underweight, and overweight was 39.6%, 18.9%, 31.2%, and 7.5% respectively. Around 16% children were concurrently stunted and wasted, 18% were both stunted and underweight and 14% were both wasted and underweight. Odds of being malnourished was higher among premature babies (stunting: AOR = 1.24, p < 0.05; wasting: AOR = 1.66, p < 0.05; underweight: AOR = 1.37, p < 0.001). More than83% children were exclusively breastfed; median duration of breastfeeding was 19.6 months and vaccination coverage were87.9%. Both undernutrition and overnutrition prevalence among under-five children in Cumilla is quite high. Health information strategies targeting young child feeding practices may be effective to minimize undernutrition quickly. Bangladesh J. Nutr. Vol. 33, December 2020, P: 1-9